Building Engagement and Resilience Through Nursing Professional Development - Laura Geron; Amelia Kim; Beth E. Jameson; Lise Cooper (Journal for Nurses in Professional Development, 2026)
This qualitative descriptive study explored how participation in evidence-based practice and innovation-focused nursing professional development programs influenced nurses' engagement, resilience, and experiences of burnout. Findings suggest that mentorship, cohort-based learning, leadership engagement, and opportunities for practice change support professional growth and sustained involvement in improvement activities. The article provides nursing professional development educators with practical strategies for designing programs that foster engagement, resilience, and workforce well-being.